Sec62 Regulates Endoplasmic Reticulum Stress and Autophagy Balance to Affect Foot-and-Mouth Disease Virus Replication - Wu, Jin’en; Zhang, Zhihui; Teng, Zhidong; Abdullah, Sahibzada Waheed; Sun, Shiqi; Guo, Huichen (Frontiers in Cellular and Infection Microbiology, 2021)
Endoplasmic reticulum (ER) stress-induced autophagy is closely associated with viral infection and propagation. However, the intrinsic link between ER stress, autophagy and viral replication during Foot-and-mouth disease virus (FMDV) infection is not fully elucidated. In previous study, we have demonstrated that FMDV infection activated the two ER stress-associated UPR of PERK-eIF2a and ATF6 signaling pathway, whereas the IRE1a signaling was suppressed. Herein, we found that the activated-ATF6 pathway directly participated in FMDV-induced autophagy and FMDV replication, while IRE1α pathway only affected FMDV replication. Further studies indicated that Sec62 was greatly reduced in the later stages of FMDV infection and blocked the activation of autophagy-related IRE1α-JNK pathway. Moreover, we also found that Sec62 promoted IRE1a phosphorylation and negatively regulated FMDV proliferation. Importantly, Sec62 directly interacted with LC3 to regulate the balance of ER stress and autophagy via fusing with lysosomes for clearance. Taken together, these results suggest that Sec62 is a critical molecule in maintenance and recovery ER homeostasis though activating IRE1α-JNK pathway and delivering autophagosome into lysosome, thus offering new insights on FMDV-host interactions and antiviral therapies.